Non-genetic effects on birth weight of MEVEZUG creole sheep in Guerrero, México - Catalán, A.; Hernández, Arelis; Fraga, L. M.; Meireles, E. J. (Cuban Journal of Agricultural Science, 2018)
A total of 1,157 records of the birth weight of 324 MEVEZUG creole sheep were used, with parturitions between 2004 and 2017, located at the Faculty of Veterinary Medicine and Zootechnics N.1 of the Autonomous University of Guerrero, Mexico. The purpose of the study was to determine the non-genetic factors that affected birth weight of lambs. A mixed generalized linear model was applied using the GLIMMIX SAS procedure, which considered birth year, birth season, parturition number, type of parturition and sex as fixed effects, and the random effect associated with each sheep. The general mean of birth weight was 2.71 kg. The studied non-genetic factors were significant (P <0.0001). The highest birth weights were obtained in the rainy season (2.48 ± 0.05 kg). Lambs born from the first calving of the sheep were less heavy, with a mean of 2.18 ± 0.04 kg. Single calving lambs were born with superior average weight (3.19 ± 0.04 kg) compared to double parturitions (2.58 ± 0.03 kg) and with triple and quadruple parturitions (2.07 ± 0.05 and 1.86 ± 0.11 kg, respectively). It is concluded that the effects of year and season of birth, parturition number, type of parturition and sex, had a significant effect on lamb birth weight. Therefore, these factors should be considered for general sheep herd management purposes, as well as for the future design of a breeding program for the MEVEZUG breed. Keywords: hair sheep, crosses, environmental factors